THE USE OF INFORMATION TECHNOLOGY AND COMMUNICATION (ICT) AND REFERENCE IN MANAGEMENT OF SCHOOLS - Fátima da Silva Batista; Wania Regina Coutinho Gonzalez (Universidade Estadual Paulista Júlio de Mesquita Filho, 2016)
This text deals with the use of Information and Communication Technologies (ICT) and its consequences both for the quality of education and to obtain awards as part of the School Management. The development of this theme was made from field research conducted with public schools managers located in different states, which had in common the fact that they obtained good evaluation, the Award in School Management. The qualitative study was conducted through observations, document analysis and semi-structured interviews, with the participation of nine managers. The relevance of this study lies particularly in contributions made in terms of subsidies for transformation processes directed to work by managers with respect to ICTs. Among the study's findings include: (a) as to how ICTs are used, showed the concern of managers that they are not separated from the school's education program; (B) in relation to the effective contribution of ICTs to obtain the prize, they revealed that their major difference in using them is the way they are incorporated into the teaching process in learning, highlighting its potential as an innovative action in the school routine.